One way in which to do this problem is to find the inverse function of G(x) first. Another, faster, method is to look at G(x) = 3x + 1. Find the x value for which y = 1:
1 = 3x + 1. Then x must equal 0. If (0, 1) satisfies G(x) = 3x + 1, then (1, 0) satisfies the inverse function of G(x) = 3x + 1.
Thus, the value of the inverse function with input 1 is 0.
Step 1: Replace "G(x)" with y.
Step 2: Solve the resulting equation for x.
Step 3: Replace x with y and y with x.
-1
Step 4: Replace this "y" with G (x).
Now replace "x" with "1".